Financing a Funded Basic Old-Age Provision via Inheritance Tax: Two Birds With One Stone? - Dirk Löhr (Wirtschaftsdienst)
Abstract In view of demographic changes, the statutory pension insurance scheme, which is financed through contributions, will soon no longer be able to ensure adequate old-age provision. By supplementing it with a funded old-age pension, citizens could participate in the returns on productive assets in old age. Corporate assets should also be fully included in inheritance tax legislation in a new reform attempt. However, the continued existence of companies should not be jeopardised. Inheritance tax on business assets could be used to finance a basic pension scheme.